PENGARUH PESAN IKLAN LAYANAN MASYARAKAT "MENGENALI, MENCEGAH, DAN MENANGANI KEKERASAN BERBASIS GENDER ONLINE (KBGO)‟ DI INSTAGRAM TERHADAP SIKAP FOLLOWERS @Cerdasberkarakter.Kemdikbudri - Hany Sya'fa, (2023)
The large number of KBGO cases against children can make them feel insecure in their surroundings, so that it can hinder their development when they are relatively young. PUSPEKA, or the Character Strengthening Center, which is an organizational unit in the Ministry of Education and Culture, is tasked with carrying out the preparation of technical policies and implementation in aspects of personality strengthening, one of which is providing education to the public on how to respond to cases of online gender-based violence with public service advertisements distributed through its Instagram account, namely @Cerdasberkarakter.Kemdibudri. This study uses the medium Theory which was developed by McLuhan with explanatory quantitative research methods. The population in this study, namely followers from the Instagram account @Cerdasberkarakter.Kemdikbudri, was then taken as a sample of 100 respondents. The results show that the correlation between variable X and variable Y has a strong relationship that is equal to 0.716. Based on the results of calculating the coefficient of determination, it shows that there is an influence of 46.7% resulting from the public service advertisement message "Recognizing, Preventing, and Dealing with Online Gender-Based Violence (KBGO)" on Instagram on followers' attitudes, while the rest can be influenced by other factors. other than this research. Then the results of the hypothesis test show that H0 is rejected and Ha is accepted, which means that there is an influence from the public service advertisement message "Recognizing, Preventing, and Dealing with Online Gender-Based Violence (KBGO)" on Instagram on follower attitudes. Therefore, it can be concluded that the public service advertisement "Recognizing, Preventing, and Dealing with Online Gender-Based Violence (KBGO)" on the Instagram Character Strengthening Center, namely @Cerdasberkaratkter.Kemdikbudri, can influence the attitude of its followers.